Dietary patterns associated with obesity outcomes in adults: an umbrella review of systematic reviews. Issue 18 (22nd December 2021) - Seifu, Canaan Negash; Fahey, Paul P; Hailemariam, Tewodros G; Frost, Steven A; Atlantis, Evan
Abstract: Objective: The aim of this umbrella review was to summarise the evidence from existing systematic reviews on the association between different dietary patterns (DP) and overweight or obesity outcomes in adults. Design: We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and searched the MEDLINE, EMBASE, CINAHL, Cochrane, Scopus, and Web of Science for systematic reviews reporting on DP and weight gain or overweight/obesity outcomes. Result: We identified 16 systematic reviews with 143 unique studies published between 2001 and 2019. Overall quality scores ranged from 4 to 10. Six reviews in 2/11 cohort and 6/19 cross-sectional studies reported (statistically significant) decreased OR for obesity (range: 0·53 to 0·73 and 0·35 to 0·88, respectively) associated with the Mediterranean diet. Five reviews in 5/15 cohort and 10/45 cross-sectional studies reported an inverse association between diet quality and weight gain or BMI ( β range: –1·3 to –0·09). Two reviews in 1/3 cohort and 1/2 cross-sectional studies reported a decreased risk of obesity (OR = 0·76) and weight gain (OR = 0·26), respectively, with fruit and vegetable intake. Five reviews of mixed DP in 3/40 cross-sectional studies reported an increased prevalence of obesity (OR = 1·19) or abdominal obesity (OR range: 1·07 to 1·27) with the Korean diet pattern. Conclusions: Our umbrella review confirms the hypothesis that Mediterranean-type DP reduce the risk of obesity in adults. Although population-specific evidence of effective interventions is needed, characteristics of Mediterranean-type DP are important considerations for national obesity prevention strategies.